The Cu2Se–PbSe–SiSe2 System and the Crystal Structure of CuPb1,5SiSe4 - Shpak, Оksana; Kogut, Yuri; Fedorchuk, Anatolii; Piskach, Liudmyla; Parasyuk, Oleg (EENU, 2014)
Isothermal section of the Cu2Se–PbSe–SiSe2 system at room temperature was investigated by X-ray diffraction. The existence of the quaternary compound was confirmed, and its composition was ascertained as CuPb1,5SiSe4. The crystal structure of CuPb1,5SiSe4 was refined by X-ray powder method (space group I 3d, a = 1,43386 nm, RI = 0,0834).
Keywords: Chalcogenides; Crystal Structure; Isothermal Section